Keterkaitan Berpikir Kreatif dan Pengetahuan Statistika dengan Kemampuan Mahasiswa STKIP Kusuma Negara Jakarta Menulis Proposal Penelitian - Y Yuliwati (LPPM STKIP Kusuma Negara, 2019)
The aim of the study is to analyze the relationships between creative thinking and statistics knowledge with the students’ competence to do the research proposal. The research was done at 5th semester students of English Education Departement of STKIP Kusuma Negara Jakarta, with the number of students were 41, defined by using cluster random sampling technique.It can be concluded that: (a) creative thinking had a significant relation with the students’ competence in doing the research proposal, (b) statistics knowledge had significant relation with the students’ competence in doing the research proposal, and (3) creative thinking and statistics knowledge had significant relation with the students’ competence in doing the research proposal.